2011
DOI: 10.1002/hbm.21007
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of the continuous Wagon Wheel Illusion: A functional MRI study

Abstract: After prolonged viewing of a continuous periodic motion stimulus at frequencies around 10 Hz, observers experience a fleeting impression of reversed motion: the continuous Wagon Wheel Illusion (c-WWI). To account for this phenomenon it has been proposed that attentional mechanisms discretely sample motion information. Alternative accounts argue that the illusion relies on the spurious activation of motion detectors, which under the effect of adaptation could trigger a reversed percept. We investigated the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…Notably, we found a large and highly significant cluster in the superior parietal lobule (SPL) related to perceptual decisions, which seems to be part of the decision network involving hMT1, either in terms of switch-related or staterelated activity. The enhanced BOLD responses in SPL in response to perceptual decisions has been previously reported in fMRI studies [Knapen et al, 2011;Lumer et al, 1998;Lumer and Rees, 1999;Reddy et al, 2011;Weilnhammer et al, 2013]. Our results seem to agree with recent studies which revealed that switch-related fronto-parietal BOLD activity can be found in relation to perceptual switches irrespective of the role of other brain regions involved in behavioral choice [Brascamp et al, 2015;Intait _ e et al, 2016].…”
Section: Discussionsupporting
confidence: 92%
“…Notably, we found a large and highly significant cluster in the superior parietal lobule (SPL) related to perceptual decisions, which seems to be part of the decision network involving hMT1, either in terms of switch-related or staterelated activity. The enhanced BOLD responses in SPL in response to perceptual decisions has been previously reported in fMRI studies [Knapen et al, 2011;Lumer et al, 1998;Lumer and Rees, 1999;Reddy et al, 2011;Weilnhammer et al, 2013]. Our results seem to agree with recent studies which revealed that switch-related fronto-parietal BOLD activity can be found in relation to perceptual switches irrespective of the role of other brain regions involved in behavioral choice [Brascamp et al, 2015;Intait _ e et al, 2016].…”
Section: Discussionsupporting
confidence: 92%
“…It is distinct from the temporal resolution of vision that underlies our perception of flicker (critical flicker fusion) or the temporal frequency limit of luminance-defined motion, among others (for review, see Holcombe, 2009). The neural basis of the temporal resolution of attention appears to lie in the posterior parietal cortex (Battelli, Pascual-Leone, & Cavanagh, 2007;Howard, Bashir, Chechlacz, & Humphreys, 2016;Reddy, Rémy, Vayssière, & VanRullen, 2011).…”
Section: Age and Gender Effect On Attentional Tracking Of One Targetmentioning
confidence: 99%
“…Third, motion adaptation can be strictly dissociated from the c-WWI: by varying stimulus contrast or eccentricity, it is possible to increase the amount of motion adaptation (as measured by both the static and the dynamic motion aftereffects) while decreasing the c-WWI, and vice versa [27]. Lastly, there is converging evidence that the neural correlates of the c-WWI primarily involve the right parietal lobe [15,28,29]; if the illusion was due to adaptation of low-level motion detectors, then its correlates would probably not be expected in such a high-level hierarchical region.…”
Section: (A) the Continuous Wagon Wheel Illusionmentioning
confidence: 99%